Intra-Individual and Seasonal Variation of Selected Biomarkers for Internal Load Monitoring in U-19 Soccer Players - Becker, Manuel; Sperlich, Billy; Zinner, Christoph; Achtzehn, Silvia (Frontiers in Physiology, 2020)
The aim of this study was to investigate intra- and inter-individual as well as inter-day and -week variation of selected biomarkers in high-performance youth soccer players to assist practitioners interpreting player´s internal load to counteract underperformance and unwanted health risks. Eleven male youth soccer players were tested multiple times during two three-week periods at midpoint (3-wkmid) and at the end (3-wkend) of the first half of a German under-19 1. Bundesliga season. The levels of creatine kinase (CK), urea and C-reactive protein (CRP) were measured during 3-wkmid and 3-wkend each Monday, Wednesday, and Friday. In 3-wkmid the CK median was 14 % higher (241 vs. 212 U/L) compared to 3-wkend (P = 0.26, ES = 0.16). Overall, the medians of CK, urea (P = 0.59, ES = 0.08) and CRP (P = 0.56, ES = 0.10) during 3-wkmid did not differ to the values of 3-wkend. Daily coefficient of variations (CVs) ranged from 22 % to 71 % (CK), 17 % to 37 % (urea) and 9 % to 164 % (CRP). Individual medians ranged from 101 to 350 U/L (CK), 23 to 50 mg/dL (urea), 0.6 to 1.1 mg/L (CRP). High intra-individual variability was demonstrated by large intra-individual CVs (medians: CK 50 %, urea 18 %, CRP 45 %). Our data show i) large inter-day and inter-week variability of all biomarkers, depending on the external load and ii) considerable inter- and intra-individual parameter variations. Creatine Kinase concentrations could sensitively reflect soccer-specific loads during the sea-son.